Urban agriculture and food security: a case study in Maringá, PR, Brazil - Neto, Paulo de Oliveira; Scalco, Andréa; Lourenzani, Ana Elissa Smith Bressan; Oliveira, Sandra Cristina de (Ciência e Natura, 2022)
The urbanization resulting from Brazilian industrialization after World War II influenced the development and infrastructure aspects of urban centers. This generated a growth of the urban population, resulting in socioeconomic structural problems related to public health, education, food insecurity, among others. Urban agriculture consists of agriculture activities within urban spaces and can promote food security to those who practice it and to those who benefit from its access. In this sense, the objective of this study was to analyze the impact of urban agriculture on food security. The research was carried out in community gardens in the city of Maringá, Brazil, using the EBIA method, with procedures of descriptive statistical analysis and multiple linear regression. The results indicate that the activity did not contribute to the food security of people who depend on the resources generated, whether for consumption or income.